EDUCATIONAL NURSING INTERVENTION TO PROMOTE ADAPTATION IN CANCER SURVIVORS: PROTOCOL FOR PILOT STUDY - Peixoto, Tiago André dos Santos Martins; Peixoto, Nuno Miguel dos Santos Martins; Pinto, Cândida Assunção Santos; Santos, Célia Samarina Vilaça de Brito (Cogitare Enfermagem, 2023)
Objective: to present the protocol of a pilot study that aims to evaluate the feasibility and acceptability of an educational nursing intervention to promote the adaptation of cancer survivors, focused on coping and anxiety. Method: this protocol was developed based on the Protocol Items: Recommendations for Interventional Trials 2013 (SPIRIT2013) Statement, in the city of Porto - Portugal, in 2022. Results: the design, structure, content, strategies, and evaluation instruments of the intervention to be implemented were defined. Conclusion: This article provides in detail the structure and content of an educational nursing intervention to promote the adaptation of cancer survivors that can be integrated into the piloting phase procedures. It can also be considered a stimulus for the development of new interventions and intervention programs in this phase of the cancer disease.